Political communication in the Roman world - Rosillo López, Cristina (Impact of Empire Ser., 2017)
"This volume aims to address the question of political communication in the Roman world. It draws upon social sciences and the current trend for the historical study of political communication. The book tackles three main problems: What constitutes political communication in the Roman world? In what ways could information be transmitted and represented? What mechanisms made political communication successful or unsuccessful? This edited volume covers questions like speech and mechanisms of political communication, political communication at a distance, bottom-up communication, failure of communication and representation of political communication. It will be of help to specialists in the Roman world, but also to students and researchers of political sciences, and specialists of political communication in pre-industrial times. Contributors are: Henriette van der Blom, Juan Manuel Cortés Copete, Cyril Courrier, Antonio Duplá Ansuategui, Martin Jehne, Julio Cesar Magalhães de Oliveira, Rosario Moreno Soldevila, Francisco Pina Polo, Cristina Rosillo-López, Catherine Steel, Jeffrey Tatum"--Provided by publisher.